Parathyroid hormone ablation alters erythrocyte parameters that are rescued by calcium‐sensing receptor gene deletion. (27th April 2013) - Romero, Jose R.; Youte, Rodeler; Brown, Edward M.; Pollak, Martin R.; Goltzman, David; Karaplis, Andrew; Pong, Lie‐Chin; Chien, Lawrence; Chattopadhyay, Naibedya; Rivera, Alicia
Abstract The mechanisms by which parathyroid hormone (PTH) produces anemia are unclear. Parathyroid hormone secretion is regulated by the extracellular Ca2+‐sensing receptor. We investigated the effects of ablating PTH on hematological indices and erythrocytes volume regulation in wild‐type, PTH‐null, and Ca2+‐sensing receptor‐null/PTH‐null mice. The erythrocyte parameters were measured in whole mouse blood, and volume regulatory systems were determined by plasma membrane K+ fluxes, and osmotic fragility was measured by hemoglobin determination at varying osmolarities. We observed that the absence of PTH significantly increases mean erythrocyte volume and reticulocyte counts, while decreasing erythrocyte counts, hemoglobin, hematocrit, and mean corpuscular hemoglobin concentration. These changes were accompanied by increases in erythrocyte cation content, a denser cell population, and increased K+ permeability, which were in part mediated by activation of the K+/Cl− cotransporter and Gardos channel. In addition we observed that erythrocyte osmotic fragility in PTH‐null compared with wild‐type mice was enhanced. When Ca2+‐sensing receptor gene was deleted on the background of PTH‐null mice, we observed that several of the alterations in erythrocyte parameters of PTH‐null mice were largely rescued, particularly those related to erythrocyte volume, K+ fluxes and osmotic fragility, and became similar to those observed in wild‐type mice. Our results demonstrate that Ca2+‐sensing receptor and parathyroid hormone are functionally coupled to maintain erythrocyte homeostasis.